Design Of Palm Shell Charcoal Media For Earthing Systems - haris, muhamad abdul; rajagukguk, managam; Gani, usman a (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
The grounding system is an important part that must be considered to ensure the safety and reliability of the operation of the electric power system. The grounding system has an influence on the smoothness and safety of the electric power system, especially when there is a disturbance related to the ground. The aim of the grounding system is to limit the voltage between the equipment and the ground to a safe condition for all operations, both normal conditions and when a disturbance occurs. . The earthing resistance value in a building is 5Î©, while for earthing electronic equipment a grounding resistance value of 3Î© is required and for lightning arrester equipment or arresters it is 1.75Î© and some devices even require an earthing resistance value of 1Î©. The design for the construction of Palm Shell Charcoal Media for Earthing Systems was made by considering several problems, such as how to reduce the resistance value to comply with standards (PUIL). One of the efforts made is to design the addition of palm oil shell charcoal with variations in hole diameter and depth of planting the charcoal in the media. The results showed that factors such as the diameter of the charcoal planting medium and the depth of rod planting had a positive influence on the resistance value. The solution that can be applied to achieve optimal earthing resistance values is to increase the diameter of the charcoal media and deepen the rod planting